Insertion Loss of Spiral Ducts - Measurements and Computations - ŁAPKA, Wojciech (Archives of Acoustics, 2009)
This work presents measured and computed characteristics of insertion loss (IL) of spiral ducts. Numerical and experimental models of spiral ducts have been investigated. For the numerical modeling, a three dimensional model computed by the use of a finite element method in a COMSOL Multiphysics computer application has been used. For the experimental modeling, there has been made a spiral duct model by using a three dimensional rapid prototyping technique. An acoustic system with a round silencer has been ivestigated, and the spiral duct has been inserted at the inlet. IL is considered in this paper as the difference between the sound pressure level (SPL) [dB] probed at only one outlet point of the acoustic system without and with an acoustical filter (spiral duct), respectively. The results of measured and computed IL of spiral ducts presented in this paper confirm the fact that this newly discovered technical solution for attenuating sound in ducted systems has an applicable potential. There are visible small discrepancies between the measurements and computations. The results can differ due to the non ideal dimensions of the experimental model and the non ideal inlet and outlet surroundings of the experimental acoustic system. However, the IL characteristics of the computed model is almost wholly covered by the IL characteristics of the measured model.